EFEKTIVITAS METODE PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM PADA MAHASISWA PENDIDIKAN AGAMA ISLAM UIN SUNAN KALIJAGA - hidayatuz, khofifah; Sholeh, Akhmad (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
This research explains the study of the effectiveness of learning methods in teachers/lecturers with Islamic Religious Education students class of 2023/2024. Knowledge and learning in the Islamic Cultural History course is something that is applied by many institutions. This history will seem boring if a student does not like it and the teacher does not have an interesting and effective learning method. This research uses an interview method with three student resource persons and two lecturers teaching the Islamic Cultural History course at PAI 2023.2024. The results of this study show that a student feels more interested and active if the method used is not rigid, such as only limited to lectures and discussions. More than that, the two lecturers applied unique methods according to the theme of the meeting and the course. The level of activeness and critical thinking of students began to be honed when a teacher provided motivation and appreciation after what was done by the two students. Grading is not always below average, but lecturers still provide good and medium grades depending on the suitability of the students. Completion of final assignments, UAS/UTS, and activeness, class attendance. This research is limited to certain majors and batches to see the level of effectiveness of learning methods on students. This research can be continued with a wider landscape at certain institutions with a particular focus.